Community Service Activities - Counseling And Random Blood Sugar Screening (Type 2 Diabetes Mellitus) - Alexander Halim Santoso; Ernawati Ernawati; Sukmawati Tansil Tan; Yohanes Firmansyah; Dean Ascha Wijaya; Fernando Nathaniel (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Diabetes mellitus is a chronic disease characterized by elevated blood sugar levels as a result of impaired insulin metabolism. Uncontrolled type 2 diabetes mellitus can result in significant complications. The purpose of the community service activities is to increase the community's knowledge, awareness, and ability to prevent, detect, and manage diabetes mellitus. This activity requires collaboration between the local community, the community service team, and medical personnel. First, the public is counseled about diabetes mellitus using effective and easy-to-understand communication methods. In addition, individuals who are at a high risk or have prediabetes are identified through early screening procedures. In addition, community service activities include providing assistance and guidance to people with diabetes mellitus. During community service activities, the effectiveness of counseling and early screening was also evaluated and monitored. This activity is anticipated to provide long-term benefits to efforts to prevent and manage diabetes mellitus in the community by utilizing a holistic approach and involving active community participation.